STUDI TERHADAP UNJUK KERJA PEMBANGKIT LISTRIK TENAGA SURYA ATAP KANTOR DESA PADANGSAMBIAN KAJA - Formasakti, Baskara; Setiawan, I Nyoman; Dwi Giriantari, Ida Ayu (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUM, 2022)
The Padangsambian Kaja Village Government in Denpasar City through the SDGs program from the Ministry of Villages, Development of Disadvantaged Regions and Transmigration has implemented clean and renewable energy. The power plant being operated is the rooftop solar power plant with a capacity of 7,2 kWp which is connected to the PLN network. The study was conducted to determine the performance of the installed solar power plant with the help of HelioScope software simulation. Energy production will be compared between the simulation results of the 2 scenarios with the results of monitoring on the inverter in the period from May to July 2021, so that it will be known the factors that influence the production of solar power plant energy. The results show the potential for energy production each year from the simulation results of scenario 1 and scenario 2 respectively are 9.964 kWh and 10.306 kWh, and the simulation results for energy production in the period from May to July in scenario 1 and scenario 2 respectively are 2.937,3 kWh and 3.057,8 kWh. Energy production from scenario 1 and scenario 2 simulation is higher than real energy production, with a difference of 180,9 kWh with a percentage of 6,1% for scenario 1, and 301,4 kWh with a percentage of 9,8% for scenario 2.